Social support, network, and relationships among coaches in different sports: a systematic review - Ferreira, João Gonçalo; Rodrigues, Filipe; Sobreiro, Pedro; Silva, Mário; Santos, Fernando Jorge; Carvalho, Gonçalo; Hernández Mendo, António; Rodrigues, José (Frontiers in Psychology, 2024)
The study aims to analyze scientific publications on the association between social networks, social relationships, and social support for sports coaches. It seeks to identify the types and levels of social support provided by various agents, and to understand the impact of this support on coaches' well-being. The goal is to help coaches better utilize social support, thereby enhancing their quality of life, work, and performance. This study systematically reviewed 11 scientific articles to investigate the association between social support, social networks, and social relationships in sports coaches. It aimed to identify the types and levels of social support offered to coaches by family members, peers, and friends. Our research utilized the PRISMA guidelines for systematic reviews and assessed study quality using the STROBE Statement. Eligibility was determined by the PECOS criterion based on the search strategy terms. Our findings indicate that social support has significant positive effects on sports coaches. It enhances self-compassion, prevents burnout symptoms, boosts job and life satisfaction, and reduces stress levels.Organizational support, characterized by clear guidelines, guidance, and autonomy, yielded positive outcomes. Conversely, the absence of social support correlated with negative outcomes for coaches, including lower self-compassion, increased stress and burnout symptoms, reduced job and life satisfaction, and heightened work-family conflict. Coaches' social networks encompassed family members, peers, friends, and other sources, with friends perceived as the most influential. Maintaining an effective social support network is crucial for coaches' performance and psychological well-being.In conclusion, this systematic review emphasizes the importance of social support for coaches in both their personal and professional lives, noting its positive effects and the negative consequences of its absence. Given the demanding nature of coaching, improving social support systems can enhance coaches' well-being and the success of sports activities.